Product design improvement method driven by online product reviews - Fang-Min Cheng; Jing Wang; Chen Chen; Guang-Rui Hu; Zi-Jun Cao (Scientific Reports)
Abstract Customer-centered design plays a crucial role in achieving sustainable design by aligning product features with actual customer needs, promoting resource efficiency, and supporting environmental protection. To better meet customer expectations and enhance satisfaction, a product design improvement method driven by online product reviews is proposed. By leveraging the unique characteristics of online reviews, customer opinions are systematically integrated into the product design improvement process, with specific integration methods developed for each stage. Using reviews of the target product and competitive products as inputs, the method progresses through five stages: review collection and attribute extraction, problem identification for the target product, competitive product analysis and case knowledge base construction, structural solution generation, and scheme decision-making. This results in a product design improvement plan that addresses both customer needs and enterprise goals. The feasibility of this approach was demonstrated through a case study involving a 3D printer product design improvement task.